Potential Outcomes of Blockchain Technology Application for Transparency of Ultimate Beneficial Owner Registration Issue - Setyowati, Milla Sepliana; Adnyani, Ida Ayu Rasthiti; Saragih, Arfah Habib; Hendrawan, Adang (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 1 (2022), 2022)
The number of High Net-Worth Individuals (HNWI) in Indonesia is increasing. However, this increase was not followed by an increase in state revenues originating from the types of income taxes related to HNWI. This issue can be overcome by applying blockchain technology. This study aims to investigate the potential outcomes of blockchain technology in the issue of Ultimate Beneficial Owner (UBO) registration. Blockchain as a technology can support tax modernization, but it has not been extensively studied. This study used a qualitative method, by using a post-positivist approach, by conducting a literature study and in-depth interviews with nine informants. The results of the study state that the potential outcomes for UBO registration consist of value delivery and risk mitigation. Value delivery is easier to realize than risk management. Both are still being discussed further to find solutions to maximize the potential outcomes. Keywords: blockchain, UBO, value delivery, risk management, tax modernization